Sistem Kontrol Suhu dan Kelembapan pada Kandang Iguana Hijau Berbasis IoT Cloud - Zen, Nur Afifah; Rifai, Muhammad; Maulana, Yulian Zetta; Permatasari, Indah (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2024)
One type of lizard that is popular in Indonesia is the green iguana, which belongs to the Iguanidae family. Green iguanas are cold-blooded animals that often sunbathe to adjust their body temperature to the same as the environmental temperature so that the iguana's digestive system can be optimal. Therefore, green iguana lovers or breeders need an IoT-based maintenance solution. This research aims to design a green iguana cage that can maintain temperature and humidity automatically using a DHT22 sensor. Based on test results, the IoT-based temperature and humidity control system in the green iguana cage was proven to be effective in maintaining environmental conditions in the cage. On the 1st day of testing, the average temperature and humidity sensor errors in the system design at three different times were 1.03% and 2.24%, respectively. Furthermore, on day 2, the average temperature and humidity sensor errors were 1.359% and 1.739% respectively. This system works effectively, where the humidifier maintains humidity by obeying the limits of turning off at humidity above 80% and turning on below 70%. Meanwhile, the light adjusts its brightness level based on temperature with a range of 30°C - 35°C. This system is able to maintain temperature and humidity with 97% accuracy. The results of the tested data are sent to the IoT Platform so that they can be accessed in real-time. The test results for the delay value of 90.45441238 ms indicate that data transmission is in the very good category.